1990
DOI: 10.1063/1.857766
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating flow with mass transfer induced by a rotating disk electrode with a superimposed time-periodic modulation

Abstract: Fluctuating flow with mass transfer induced by a rotating disk electrode with a time-periodic angular velocity Ω0[1+α cos(pτ)]b is analyzed by solving numerically the time-dependent von Kármán self-similar form of the Navier–Stokes and convective diffusion equations when the electrochemical reaction at the disk electrode is mass transfer limited. Results are presented for the full frequency range for several values of the waveform parameter b and α<1. At the intermediate frequency p=1.24 (with α=0.9, b=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…This situation results in an axisymmetric von Kármán similarity flow that is governed by the nondimensional equations 4,11,12,14 …”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…This situation results in an axisymmetric von Kármán similarity flow that is governed by the nondimensional equations 4,11,12,14 …”
Section: Theorymentioning
confidence: 99%
“…12,13 However, experimental corroboration of the predicted nonlinear electrochemical response has been limited to a few modulation frequencies. [12][13][14] The only fullspectrum nonlinear frequency response experiments for a speed-modulated RDE focused solely on the time-averaged ͑mean͒ limiting current, not oscillating components; experiments confirmed that 0 Ϸ 2⍀ 0 was a key resonant frequency for the steady streaming flow generated by the time-averaged Reynolds stresses. 15 To the best of our knowledge, nobody has investigated the full-spectrum frequency response of electrochemical higher harmonics.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Chawla and Verma [5] undertook an exhaustive study of this physical situation and derived specific expressions for quantities of physical interest under various asymptotic conditions. Shwartz, Rehg, Stroeve and Higgins [6] analyzed, numerically and experimentally, the fluctuating flow with mass transfer induced by a rotating disk electrode with a superposed time-periodic angular velocity. Their efforts at comparing their numerical results, with the low and high frequency asymptotic theories of Chawla and Verma [5], were rather fruitless because they overlooked some of the terms of higher order in the solution of Chawla and Verma.…”
Section: Introductionmentioning
confidence: 99%